Assessment of Adipocyte Transduction Using Different AAV Capsid Variants - Stanislav Boychenko; Alina Abdullina; Viktor S. Laktyushkin; Andrew Brovin; Alexander D. Egorov (MDPI AG, 2024)
Background/Objectives: Adeno-associated viruses (AAVs) are widely used as viral vectors for gene delivery in mammalian cells. We focused on the efficacy of the transduction of AAV2/5, 2/6, 2/8 and 2/9 expressing GFP in preadipocyte cells by live imaging microscopy using IncuCyte S3 and flow cytometry. Methods: Three transduction modes in 3T3-L1 preadipocyte cells assessed: AAV transduction in 3T3-L1 preadipocyte cells, transduction with further differentiation into mature adipocyte-like cells and the transduction of differentiated 3T3-L1 adipocytes. For the in vivo study, we injected AAV2/6, AAV2/8 and AAV2/9 in adipose tissue of C57BL6 mice, and the transduction capacity of AAV2/6, along with AAV2/8 and AAV2/9 was evaluated. Results: AAV2/6 demonstrated the highest transduction efficiency in 3T3-L1 preadipocytes, as it was 1.5-2-fold more effective than AAV2/5, and AAV2/8 in the range of viral concentrations from 2 × 104 to 1.6 × 105 VG/cell. AAV2/5 and AAV2/8 showed transduction efficiencies similar to each other. The expression of GFP under the CMV promoter remained stable for up to 20 days. The induction of 3T3-L1 differentiation in three days after AAV transduction did not alter the GFP expression level, and AAV2/6 showed the best transduction efficiency. AAV2/6 demonstrated the ability to transduce mature adipocytes. These results were confirmed by in vivo studies on C57BL6 mice. AAV2/6 had the highest transducing activity on both inguinal and interscapular adipose tissue. Conclusions: Thus, AAV2/6 has demonstrated higher transduction efficacy compared to AAV2/5, AAV2/8 and AAV2/9 both in 3T3-L1 adipocytes and adipose tissue in vivo, which proves its usability along with AAV2/8 and AAV2/9 for gene delivery to adipocytes.